Molecular analysis of Dystrophin gene in patients with Duchenne muscular dystrophy - Salmi, Ab Aziz (Universiti Sains Malaysia, 2006)
Duchenne muscular dystrophy (DMD) is an inherited disorder characterized by rapidly progressive muscle weakness, which start in the legs and pelvis and later affects the whole body. The responsible gene for DMD has been mapped on the Xp21, namely dystrophin gene. This gene is the largest gene in human being, comprises 79 exons. The function of the gene is to enable muscle fibers to make a protein called dystrophin protein. Muscle fibers in people affected with DMD are extremely deficient of dystrophin protein. Seven exons were found to be the most commonly deleted in patients from South East Asia populations and we choose these seven exons for this study. The seven exons are exon 44, 43, 45, 46, 49, 50, and 51. Seven DMD patients from Malaysia were recruited as our patients of study. Sec of blood were taken from these patients, DNA were extracted using kit (QiaAMP mini kit). Polymerase Chain Reaction (PCR) was performed to analyze the mutation of dystrophin gene in DMD patients. The objective is to detect the deletion of the seven hotspot exons of the dystrophin gene. We found that the two patients with deletion of all the tested exons. Three patients had at least two deleted while two did not show deletion of any of the seven exons tested. The two patients who did not show any deletion could not be excluded from DMD, as there could be other types of mutation in the Dystrophin gene, which is not tested in this study.